Tingkat Kecemasan Ibu dalam Menghadapi Banjir di Kelurahan Sangkrah Kota Surakarta - Cindyana Putri Sinta; Dyah Rahmawatie Ratna Budi Utami (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
Disaster preparedness is a series of activities implemented to anticipate disasters by virtue of organization, and efficient and effective steps. Disaster preparedness may reduce the anxiety level in dealing with natural disasters. The purpose of this study is to understand the correlation between disaster preparedness and the level of mothers' anxiety in dealing with floods in Sangkrah village. This study is a quantitative research using a descriptive correlational method and a cross-sectional approach. The sampling technique used is the proportionate stratified random sampling technique. The sample of this study are mothers affected by floods in Sangkrah village since 2021. The data analysis technique used is Spearman's rho metric. The results of this study indicate that the majority of maternal disaster preparedness in Sangkrah Village is in the high category, namely 257 respondents (70.4%). The majority of maternal anxiety in Sangkrah Village is in the moderate category, namely 244 respondents (66.8%). The Spearman Rho test results obtained a value of 0.000 which means a value <0.05. This study concludes that there is a relationship between disaster preparedness and the level of maternal anxiety in dealing with flooding in Sangkrah Village.